COMPARATIVE ANALYSIS OF COMPLICATIONS IN PATIENTS AFTER INDIVIDUAL ONCOLOGICAL AND MODULAR ONCOLOGICAL ENDOPROSTHETICS OF THE KNEE JOINT WITH TUMOR LESIONS - Oleksandr Buryanov; Obada Mohammad Bishtawi; Volodymyr Protsenko; Yevhen Solonitsyn (Bogomolets National Medical University, 2020)
The article contains analysis of complications after individual oncological knee joint endoprosthesis replacement in cases of tumor lesions. Complications were observed in 45 ,8% of cases after knee joint endoprosthesis replacement operations with tumor lesions. The main complications that were observed included infectious ones: 18,1%, aseptic instability of the endoprosthesis stem:  16,7%, bone fracture at the site of endoprosthesis stem implantation: 6,9%, destruction of the endoprosthesis structure: 4,2%. The factors that led to complications, as well as methods of their elimination are given. Dialysis and a long course of antibiotic therapy or the installation of a metal-cement spacer device followed by repeated endoprosthesis replacement is advised in case of an infectious complication. Repeated joint endoprosthesis replacement with replacement of only one (loose) component of the endoprosthesis, using a long intramedullary stem or replacement of the total endoprosthesis is advised in case of aseptic instability of the endoprosthesis stem. Metallic osteosynthesis of the  periprosthetic bone fracture is performed using bone plates  and cable grip in cases of bone fracture at the site of endoprosthesis stem implantation. Repeated joint endoprosthesis replacement is effected with replacement of the entire endoprosthesis structure in case of destruction of the endoprosthesis structure.